Antioxidant Characteristics and Identification of Peptides from Sorghum Kafirin Hydrolysates. Issue 8 (17th July 2019) - Xu, Shiwei; Shen, Yanting; Chen, Gengjun; Bean, Scott; Li, Yonghui
Abstract : Abstract: Grain sorghum is gaining interest for various uses as a highly sustainable crop. Kafirin is the main storage protein in grain sorghum. However, the antioxidant activities of kafirin hydrolysates have not been systematically investigated. The objectives of this study were to characterize the antioxidative hydrolysates and their ultrafiltrated fractions from sorghum kafirin using chemical assays and model systems and to identify the representative peptides. Kafirin Neutrase hydrolysates displayed promising yield and antioxidant capacity among those prepared with several different proteases. The effects of critical variables including protein substrate content, enzyme‐to‐substrate ratio, and reaction time on antioxidant production were studied. Selected hydrolysates were further fractionated through ultrafiltration and gel filtration chromatography (GFC). Medium‐sized fraction (3 to 10 kDa) revealed relatively higher total phenolic content and stronger antioxidative activities with regard to free radical scavenging activity, metal ion chelating activity, reducing power, and oxygen radical absorbance capacity. In an oil‐in‐water emulsion system, incorporation of selected fraction of hydrolysates inhibited the formation of primary and secondary oxidation products by 83.03% and 65.59%, respectively, by the end of a 14‐day incubation period. Similar oxidation inhibition effect was also observed in a ground meat system. Peptide compositions of the most promising fraction from GFC and reversed‐phase high‐performance liquid chromatography were identified using matrix‐assisted laser desorption ionization–time of flight/time of flight mass spectrometry. Practical Application: This study provided a feasible approach to produce peptide antioxidants from sorghum kafirin. The novel naturally derived antioxidants could be potentially used as alternatives or synergetic components to synthetic antioxidants in improving the oxidative stability of various food products.